Carbon Fibers - Park, Soo-Jin (Springer, 2015)
This book contains eight chapters that discuss the manufacturing methods, surface treatment, composite interfaces, microstructure-property relationships with underlying fundamental physical and mechanical principles, and applications of carbon fibers and their composites. Recently, carbon-based materials have received much attention for their many potential applications. The carbon fibers are very strong, stiff, and lightweight, enabling the carbon materials to deliver improved performance in several applications such as aerospace, sports, automotive, wind energy, oil and gas, infrastructure, defense, and semiconductors. However, the use of carbon fibers in cost-sensitive, high-volume industrial applications is limited because of their relatively high costs. However, its production is expected to increase because of its widespread use in high-volume industrial applications; therefore, the methods used for manufacturing carbon fibers and carbon-fiber-reinforced composites and their structures and characteristics need to be investigated.